2016
DOI: 10.1136/tobaccocontrol-2016-053174
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' interest in trying flavoured e-cigarettes

Abstract: Background More U.S. adolescents use e-cigarettes than smoke cigarettes. Research suggests flavored e-cigarettes appeal to youth, but little is known about perceptions of and reasons for attraction to specific flavors. Methods A national sample of adolescents (n=1,125) ages 13-17 participated in a phone survey from November 2014-June 2015. We randomly assigned adolescents to respond to survey items about 1 of 5 e-cigarette flavors (tobacco, alcohol, menthol, candy, or fruit) and used regression analysis to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
204
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(214 citation statements)
references
References 25 publications
(19 reference statements)
7
204
1
2
Order By: Relevance
“…All e-cigarette advertisements depicted either an e-liquid container or e-cigarette; all cigarette advertisements depicted either a cigarette pack or cigarette. E-cigarette advertisements were for sweet (i.e., candy/desserts) and fruit flavor e-cigarettes, based on evidence of the appeal of these flavors to youth compared with other flavors (Krishnan-Sarin et al, 2015; Pepper et al, 2016; Vasiljevic et al, 2016), and testing only these top flavor preferences also reduced differences in novelty between sweet/fruit and tobacco flavor e-cigarette advertisements; tobacco flavor e-cigarette advertisements depicted tobacco, tobacco plants, leaves or crops. Control images of sweets, fruits, and mint with no tobacco product were taken from online image sources to match the background images of sweet/fruit flavor e-cigarette advertisements and menthol cigarette advertisements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All e-cigarette advertisements depicted either an e-liquid container or e-cigarette; all cigarette advertisements depicted either a cigarette pack or cigarette. E-cigarette advertisements were for sweet (i.e., candy/desserts) and fruit flavor e-cigarettes, based on evidence of the appeal of these flavors to youth compared with other flavors (Krishnan-Sarin et al, 2015; Pepper et al, 2016; Vasiljevic et al, 2016), and testing only these top flavor preferences also reduced differences in novelty between sweet/fruit and tobacco flavor e-cigarette advertisements; tobacco flavor e-cigarette advertisements depicted tobacco, tobacco plants, leaves or crops. Control images of sweets, fruits, and mint with no tobacco product were taken from online image sources to match the background images of sweet/fruit flavor e-cigarette advertisements and menthol cigarette advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…Youth were early experimenters who had tried an e-cigarette and were susceptible to future e-cigarette use, based on findings that susceptibility predicts initiation and progression of e-cigarette use (Bold et al, 2016). fMRI was used to test the hypothesis that NAc response would be greater for sweet/fruit versus tobacco flavor e-cigarette advertisements, based on reported preferences for sweet and fruit flavor e-cigarettes as compared with other flavors of e-cigarettes, among youth (Krishnan-Sarin et al, 2015; Pepper et al, 2016; Vasiljevic et al, 2016). Menthol and regular cigarette advertisements and images of fruits and sweets with no tobacco product were used as controls.…”
Section: Introductionmentioning
confidence: 99%
“…5 Flavored tobacco products are viewed favorably by users 6 and are perceived by youth to be less harmful to health than non-flavored products. 7 Furthermore, sales of these products appear be driving the growth of non-cigarette tobacco use among youth, young adults and adults. 8-15 …”
mentioning
confidence: 99%
“…Pepper et al 21 used a national phone survey in 1125 adolescents aged 13–17 to explore reasons for the appeal of specific e-cigarette flavours. They found that adolescents were more likely to report interest in trying an e-cigarette when offered by a friend if flavoured with menthol, candy or fruit compared with traditional tobacco flavour.…”
mentioning
confidence: 99%